Empowering Africa's food systems for the future - von Braun, Joachim; Ulimwengu, John M.; Babu, Suresh Chandra; Srivastava, Nandita; Swinnen, Johan; Blumenthal, Nick; Nwafor, Apollos; Nhlengethwa, Sibusiso; Kapuya, Tinashe; Mutyasira, Vine; Haddad, Lawrence; Keizire, Boaz B.; et al. (Alliance for a Green Revolution in Africa, 2023)
Africa, a continent of immense potential, stands at a crucial juncture. Home to some of the world’s most fertile lands, abundant resources, and a burgeoning young population, it remains paradoxically ensnared in the grip of food insecurity, malnutrition, and challenges such as climate change, post-harvest losses, and inefficient supply chains. The urgency to empower and transform African food systems is not merely an agricultural or economic imperative but a moral, social, and ecological one. The 2023 report, “Empowering Africa Food Systems for the Future,” highlights the ways in which Africa is uniquely positioned to redefine its future and pave a sustainable and resilient path for generations to come. In delving into the assessment of food systems failures, the report confronts some harsh truths. Despite being home to nearly 60 percent of the world’s uncultivated arable land, Africa remains a net food importer spending billions annually to meet its food demands. A large fraction of its population still grapples with chronic hunger and malnutrition. Yet, it does not stop at just assessing failures; it moves forward to take stock of the robust and diverse food systems that form the lifeblood of the continent.